2012
DOI: 10.1007/s00125-012-2591-4
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of enteroviruses in the intestine of patients with type 1 diabetes

Abstract: Aims/hypothesis The purpose of this study was to investigate whether the gut mucosa is a reservoir for enterovirus persistence in patients with type 1 diabetes. Methods Small intestine biopsy samples from 25 individuals at different stages of type 1 diabetes, 21 control individuals and 27 individuals with coeliac disease were analysed for the presence of enterovirus RNA by using both radioactive in-situ hybridisation and real-time RT-PCR and for the presence of enterovirus proteins by immunostaining with antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…A recent report shows that a large proportion of type 1 diabetic patients have prolonged/persistent enterovirus infection associated with an inflammatory process in the gut mucosa, suggesting that the gut mucosa is a reservoir for enterovirus persistence in patients with type 1 diabetes [8], [9]; however these findings have not been confirmed in another study [10].…”
Section: Introductionmentioning
confidence: 87%
“…A recent report shows that a large proportion of type 1 diabetic patients have prolonged/persistent enterovirus infection associated with an inflammatory process in the gut mucosa, suggesting that the gut mucosa is a reservoir for enterovirus persistence in patients with type 1 diabetes [8], [9]; however these findings have not been confirmed in another study [10].…”
Section: Introductionmentioning
confidence: 87%
“…EV RNA-positive samples were more frequent among the cases than among the controls.Oikarinen et al, 2012 [98]EVLarge proportion of type 1 diabetes patients have prolonged/persistent EV infection associated with an inflammation process in gut mucosa.Mercalli et al, 2012 [99]EVSmall intestine biopsy samples from 25 individuals at different stages of type 1 diabetes, 21 controls and 27 individuals with coeliac disease analysed for the presence of EV RNA by in situ hybridisation and RT-PCR. Prolonged/persistent EV infections in gut mucosa are not common in patients with type 1 diabetes.Viskari et al, 2000 [100]EVThe rapid decrease in EV infection frequency in Finland may explain the increasing incidence of type 1 diabetes.Roivainen et al, 2002 [101]EVPatterns and consequences of EV infections investigated in cultured adult human isolated islets.…”
Section: How Can the Histopathological Hallmarks Of Diabetes Be Explamentioning
confidence: 99%
“…Epidemiological studies have suggested that infections with enteroviruses, in particular those of the coxsackie B virus (CVB) serotypes, may be linked to islet autoimmunity and development of type 1 diabetes [1][2][3][4][5]. Other observations suggesting that infections with these viruses have a causative role in diabetes development come from studies that found enteroviruses more frequently in pancreases [6][7][8] and, in some studies, also gut biopsies [9][10][11], from patients with type 1 diabetes compared with healthy controls. Some enteroviruses, including the CVBs, are pancreatropic and can infect human beta cells in vitro, often with a detrimental outcome (e.g.…”
Section: Introductionmentioning
confidence: 99%